Prevalence and correlates of simultaneous, multiple substance injection (co‐injection) among people who inject drugs in Melbourne, Australia. (27th August 2020) - Palmer, Anna; Higgs, Peter; Scott, Nick; Agius, Paul; Maher, Lisa; Dietze, Paul
Abstract: Aims: To estimate the prevalence of and risk factors associated with concurrent injection of multiple substances (co‐injection) among a community‐recruited cohort of people who inject drugs. Design: Cross‐sectional study. Setting: Melbourne, Australia. Participants: A sample of 720 actively injecting participants from the Melbourne Injecting Drug User Cohort Study (33% female) was extracted. Measurements: We constructed two statistical models: a logistic regression model analysing correlates of co‐injection of any substance combination in the past month and a multinomial logistic regression model analysing correlates of three mutually exclusive groups: heroin–diphenhydramine co‐injection only, co‐injection of other substances and no co‐injection. Risk factors examined included drug use characteristics, demographic characteristics, health service use, hepatitis C status, injection risk behaviours and previous experience of non‐fatal overdose. Findings: One‐third [ n = 226, 31%; 95% confidence interval (CI): 28–34%] of participants reported co‐injecting substances within the past month, with equal numbers of participants reporting injecting combinations of heroin–diphenhydramine ( n  = 121, 54%; 95% CI = 48–60%) and heroin–methamphetamine ( n  = 121, 54%; 95% CI = 48–60%). In logistic regression analyses, reporting co‐injection of any substance combination was associated with male sex [adjusted odds ratio (aOR) = 1.80, 95% CI = 1.18–2.74, P  = 0.006] and injecting daily or more frequently (aOR = 2.04, 95% CI = 1.31–3.18, P  = 0.002). In multinomial logistic regression analyses, participants reporting heroin–diphenhydramine co‐injection only were significantly more likely to report groin injecting [adjusted relative risk ratio (aRRR) = 6.16, 95% CI = 2.80–13.56, P  < 0.001] and overdose (requiring an ambulance) in the past 12 months (aRRR = 2.81, 95% CI = 1.17–6.72, P  = 0.021) compared with participants reporting no co‐injection or co‐injection of other substances. Conclusions: A substantial proportion of people who inject drugs report co‐injection of multiple substances, which is associated with a range of socio‐demographic, drug use and health service use risk factors.